KOLONIALISME DALAM PUSARAN KONFLIK PEMBAHARUAN ISLAM: Menelususri Keterlibatan dan Peran Belanda dalam Keberlangsungan Konflik yang Terjadi di Minangkabau - Ihsan Sanusi (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2018)
At the beginning of the conflict in the Minangkabau realm, only fellow brothers and sisters (brother conflict), fellow community members. However, this was widespread, and subsequently changed significantly with the interference of foreign powers. Foreign interference itself, basically it cannot be separated from the demands of the adat (traditional leaders or the leaders). How to explain and understand all this? Of course it's not too difficult to understand. Because, in fact with the increasing Paderi movement, many traditional leaders were eliminated, then expelled or even ran away, because they did not want to be victims of Paderi's radicaslism. Between those who fled, there were those who sought relations with foreigners, first with Raffles in Bengkulu, then also when Britain was entrenched in Padang. Next, with Du Puy in Padang when the Dutch returned to West Sumatra. The conflict of the rise of Islam in Minangkabau became increasingly complex with the influx of foreign influences - especially the Dutch, who wanted to instill power in Minangkabau. Dutch power, has become a kind of third party that plays a role in the continuation of the conflict of renewal of Minangkabau Islam. The facts above are also strengthened by various proofs of the involvement and role of the Dutch in the war against the Padrians. In addition, there was a testimony from the Dutch people themselves, who had served in the Minangkabau.